Analytical models for multi-slice helical CT performance parameters - Hsieh, Jiang (Medical physics (Lancaster), 2003)
One of the most recent technological advancements in computed tomography (CT) is the introduction of multi-slice CT (MSCT). When combined with the helical scan mode, MSCT offers significant improvements in volume coverage, isotropic spatial resolution, and contrast utilization. Although experimental studies have been conducted on MSCT performance, there is a lack of theoretical analysis on the slice sensitivity profile (SSP) and noise performance. In this paper, we derive several closed-form expressions, for linear interpolation based helical reconstruction algorithms, to characterize these performance parameters under different detector configurations and acquisition modes. Following the common practice, the expressions are explicitly described for regions near the iso-center, although the same approach can be used to describe system performances away from the iso-center. These models are validated against phantom experiments.